2008
DOI: 10.1186/1471-2180-8-184
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm development by potentially pathogenic non-pigmented rapidly growing mycobacteria

Abstract: BackgroundA study to evaluate the biofilm-development ability in three different media (Middlebrook 7H9, sterile tap water and PBS-5% glucose) was performed with 19 collection strains from 15 different species on non-pigmented rapidly growing mycobacteria (NPRGM). A microtiter plate assay was developed to evaluate the percentage of covered surface of the microtiter plate wells in different days from day 1 to day 69.ResultsAll strains were able to develop biofilm in all the tested media. Middlebrook 7H9 showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 42 publications
(50 reference statements)
2
47
2
Order By: Relevance
“…While biofilm formation may depend on growth conditions 18, substrates, and M. abscessus strains, these data suggest that M. abscessus is capable of expressing a more virulent phenotype in the presence of neutrophils. In contrast to an earlier report that biofilm formation by M. abscessus occurred over a period of weeks [50], we found that in the presence of neutrophils, M. abscessus biofilms could form quickly in conditions more closely resembling the nutrient rich CF airway or inflamed tissue. These data suggest that initial and established infections may exploit the neutrophil-rich environment to maintain an infectious state.…”
Section: Discussioncontrasting
confidence: 99%
“…While biofilm formation may depend on growth conditions 18, substrates, and M. abscessus strains, these data suggest that M. abscessus is capable of expressing a more virulent phenotype in the presence of neutrophils. In contrast to an earlier report that biofilm formation by M. abscessus occurred over a period of weeks [50], we found that in the presence of neutrophils, M. abscessus biofilms could form quickly in conditions more closely resembling the nutrient rich CF airway or inflamed tissue. These data suggest that initial and established infections may exploit the neutrophil-rich environment to maintain an infectious state.…”
Section: Discussioncontrasting
confidence: 99%
“…In the biofilm, these genes can be activated through the bacterial quorum system, and bacteria can develop phenotypic resistance even in strains that appeared to be antibioticsusceptible in common antimicrobial susceptibility tests. Because these mycobacteria are able to develop biofilms [16], the presence of efflux pump genes in these strains could be a resistance mechanism that leads to clinical failures despite in vitro susceptibility of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…M. abscessus is potentially exposed to reactive oxygen species in macrophages and in the environment. The bacterium is found in biofilms and water distribution systems (Esteban et al, 2008;Fraser et al, 1992;Greendyke & Byrd, 2008;Howard et al, 2006;Vaerewijck et al, 2005), and reactive oxygen species are generated in biofilms (Cáp et al, 2012;Das & Manefield, 2012;Zhu & Kreth, 2012), and the chlorine used in municipal water purification is also an oxidant. We conducted preliminary experiments comparing the resistance of Dnd-positive and Dnd-negative isolates of M. abscessus sensu stricto to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%